The checkered beetles (Coleoptera: Cleridae) of the Maritime Provinces of Canada - Majka, Christopher G. (Zootaxa, 2006)
The beetles of the family Cleridae in the Maritime Provinces of Canada are reviewed and new provincial records are reported. As a result, 16 taxa (15 species and one additional subspecies) are now known to occur in the region. A total of 19 new provincial records are reported; seven from Prince Edward Island, nine from Nova Scotia, and three from New Brunswick. Three species, Zenodosus sanguineus (Say), Necrobia rufipes (DeGeer), and Necrobia violacea (Linnaeus) are newly recorded in the Maritime Provinces. The bionomics of the fauna is briefly reviewed; species found in the region fall into one of five ecological groups. The composition of the fauna is also examined in relation to subjects such as island faunas, the northeastern North American regional fauna, and adventive species.